2019
DOI: 10.2169/internalmedicine.1001-18
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced Autoimmune Hemolytic Anemia and Hemophagocytic Lymphohistiocytosis in Non-small Cell Lung Cancer

Abstract: We herein report a 78-year old man with squamous cell carcinoma of the lungs treated with pembrolizumab. At 10 days after the administration of pembrolizumab, he showed progressive anemia and increased levels of bilirubin. Because the findings of a direct coombs test and cold hemagglutinin were positive, we diagnosed the patient with autoimmune hemolytic anemia and treated him with prednisolone. Subsequently, he was admitted to our hospital owing to fatigue, a high fever, and jaundice. His clinical findings me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…On literature review, the case reports discussing immunotherapy-induced HLH have described a wide range of underlying malignancies including Squamous Cell Carcinoma of the Lung, Urothelial Carcinoma, Thymic Carcinoma, Merkel Cell Carcinoma, Breast Cancer, and Melanoma however to our knowledge this is the first report of immunotherapy-induced HLH in a HNSCC patient [3][4][5][6][7][8][9][10][11]. The time to HLH onset after starting immunotherapy has been shown to be highly variable, ranging from less than a month after receiving either pembrolizumab, nivolumab, or combination ipilimumab/nivolumab to over a year in a patient treated with pembrolizumab [3,4,7]. Interestingly, some case reports discuss patients who became critically ill requiring ICU management due to complications of HLH who not only recovered with steroids but also demonstrated tumor regression, with some suggesting that the degree of antitumor efficacy with checkpoint inhibitors may correlate with the severity of side effects patient's experience [4,9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On literature review, the case reports discussing immunotherapy-induced HLH have described a wide range of underlying malignancies including Squamous Cell Carcinoma of the Lung, Urothelial Carcinoma, Thymic Carcinoma, Merkel Cell Carcinoma, Breast Cancer, and Melanoma however to our knowledge this is the first report of immunotherapy-induced HLH in a HNSCC patient [3][4][5][6][7][8][9][10][11]. The time to HLH onset after starting immunotherapy has been shown to be highly variable, ranging from less than a month after receiving either pembrolizumab, nivolumab, or combination ipilimumab/nivolumab to over a year in a patient treated with pembrolizumab [3,4,7]. Interestingly, some case reports discuss patients who became critically ill requiring ICU management due to complications of HLH who not only recovered with steroids but also demonstrated tumor regression, with some suggesting that the degree of antitumor efficacy with checkpoint inhibitors may correlate with the severity of side effects patient's experience [4,9].…”
Section: Discussionmentioning
confidence: 96%
“…The time to HLH onset after starting immunotherapy has been shown to be highly variable, ranging from less than a month after receiving either pembrolizumab, nivolumab, or combination ipilimumab/nivolumab to over a year in a patient treated with pembrolizumab [3,4,7]. Interestingly, some case reports discuss patients who became critically ill requiring ICU management due to complications of HLH who not only recovered with steroids but also demonstrated tumor regression, with some suggesting that the degree of antitumor efficacy with checkpoint inhibitors may correlate with the severity of side effects patient's experience [4,9]. Specific risk factors for development of HLH related to immunotherapy are currently unknown, however one case report describes a patient with breast cancer who developed HLH from pembrolizumab, recovered following a course of steroids, and underwent molecular genetic testing with subsequent discovery of a PRFA91V polymorphism [6].…”
Section: Discussionmentioning
confidence: 99%
“…According to the HLH‐2004 protocol, high‐dose glucocorticoids, etoposide, methotrexate, and cyclosporine are the major drugs included in the treatment plan, but HPS/HLH is often refractory to treatment. In contrast, irHPS responds well to steroid therapy, and many studies have reported that it could be treated with high‐dose steroid therapy alone ( 11,15,16 and 13 ). Our patient was also completely cured by steroid therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them involved melanoma and bladder cancer (12,13). The other one referred to a lung cancer patient on pembrolizumab without rheumatologic conditions (14). In the literature, PD-L1 inhibitors have long been described in the context of their T-cell activating effects.…”
Section: Discussionmentioning
confidence: 99%